Modulating the Heat Sensitivity of Prostate Cancer Cell Lines In Vitro: A New Impact for Focal Therapies - Oliver Hahn; Franziska M. Heining; Jörn Janzen; Johanna C. R. Becker; Marina Bertlich; Paul Thelen; Josef J. Mansour; Stefan Duensing; Sascha Pahernik; Lutz Trojan; Ionel V. Popeneciu (Biomedicines, 2020)
Focal therapies such as high-intensity focused ultrasound (HiFU) are an emerging therapeutic option for prostate cancer (PCA). Thermal or mechanical effects mediate most therapies. Moreover, locally administered drugs such as bicalutamide or docetaxel are new focal therapeutic options. We assessed the impact of such focal medical treatments on cell viability and heat sensitivity by pre-treating PCA cell lines and then gradually exposing them to heat. The individual heat response of the cell lines tested differed largely. Vertebral-Cancer of the Prostate (VCaP) cells showed an increase in metabolic activity at 40–50 °C. Androgen receptor (AR)-negative PC3 cells showed an increase at 51.3 °C and were overall more resistant to higher temperatures. Pre-treatment of VCaP cells with testosterone (VCaPrev) leads to a more PC3-like kinetic of the heat response. Pre-treatment with finasteride and bicalutamide did not cause changes in heat sensitivity in any cell line. Mitoxantrone treatment, however, shifted heat-induced proliferation loss to lower temperature in VCaP cells. Further analysis via RNAseq identified a possible correlation of heat resistance with H3K27me3-dependent gene regulation, which could be related to an increase in the histone methyltransferase EZH2 and a possible neuroendocrine differentiation. Pre-treatment with mitoxantrone might be a perspective for HiFU treatment. Further studies are needed to evaluate possible combinations with Hsp90 or EZH2 inhibitors.